Recent trends in the nanozeolites-based oxygen concentrators and their application in respiratory disorders - Yadav, Virendra Kumar; Choudhary, Nisha; Inwati, Gajendra Kumar; Rai, Ashita; Singh, Bijendra; Solanki, Bharat; Paital, Biswaranjan; Sahoo, Dipak Kumar (Frontiers in Medicine, 2023)
Medical-grade oxygen is the basic need for all medical complications, especially in respiratory-based discomforts. There was a drastic increase in the demand for medical-grade oxygen during the current pandemic. The non-availability of medical-grade oxygen led to several complications, including death. The oxygen concentrator was only the last hope for the patient during COVID-19 pandemic around the globe. The demands also are everlasting during other microbial respiratory infections. The yield of oxygen using conventional molecular zeolites in the traditional oxygen concentrator process is less than the yield noticed when its nano-form is used. Nanotechnology has enlightened hope for the efficient production of oxygen by such oxygen concentrators. Here in the current review work, the authors have highlighted the basic structural features of oxygen concentrators along with the current working principle. Besides, it has been tried to bridge the gap between conventional oxygen concentrators and advanced ones by using nanotechnology. Nanoparticles being usually within 100 nm in size have a high surface area to volume ratio, which makes them suitable adsorbents for oxygen. Here authors have suggested the use of nano zeolite in place of molecular zeolites in the oxygen concentrator for efficient delivery of oxygen by the oxygen concentrators.